A Photodynamic System based on Endogenous Bioluminescence for in vitro Anticancer Studies. Issue 18 (14th October 2019) - Lin, Wenxin; Gong, Jianqiu; Fang, Liquan; Jiang, Ke
Abstract : Photodynamic therapy (PDT) is becoming an important cancer treatment in recent years. However, at present, the therapeutic effect of PDT is limited due to insufficient penetration depth of light. In this study, a new photodynamic system (d ‐Lu)PCN‐224 is constructed by porphyrin‐based metal‐organic framework (MOF) PCN‐224 and bioluminescent moleculed ‐fluorescein (d ‐Lu). The bioluminescence (BL) spectrum of the reaction overlaps with the absorption spectrum of PCN‐224, so it is speculated that bioluminescence resonance energy transfer (BRET) between the MOF andd ‐Lu which indicates inner light can be gained and used for PDT. Confocal imaging analysis and cytotoxicity assays have demonstrated that (d ‐Lu)PCN‐224 can produce singlet oxygen and decrease the cell viability of SKOV‐3. This system provides a possibility of PDT for deep‐level organization without an external light source. Abstract :